1995
DOI: 10.1172/jci118180
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human lecithin-cholesterol acyltransferase in transgenic mice. Effect of human apolipoprotein AI and human apolipoprotein all on plasma lipoprotein cholesterol metabolism.

Abstract: IntroductionHuman (Hu) lecithin-cholesterol acyltransferase (LCAT) is a key enzyme in the plasma metabolism of cholesterol. To assess the effects of increased plasma levels of LCAT, four lines of transgenic mice were created expressing a Hu LCAT gene driven by either its natural or the mouse albumin enhancer promoter. Plasma LCAT activity increased from 1. The physiologic substrates for LCAT are nascent and mature HDL. Human (Hu) HDL is very heterogeneous both in particle size (5) and protein composition (6). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 43 publications
5
50
0
Order By: Relevance
“…In rodent models, there is an inverse relationship between fasting plasma TG levels and the murine lcat gene dose (6). Furthermore, transgenic mouse and rabbit models with overexpression of the human LCAT gene have been found to have a modest reduction in fasting TG (8,9). The mechanism by which LCAT modulates TG metabolism has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent models, there is an inverse relationship between fasting plasma TG levels and the murine lcat gene dose (6). Furthermore, transgenic mouse and rabbit models with overexpression of the human LCAT gene have been found to have a modest reduction in fasting TG (8,9). The mechanism by which LCAT modulates TG metabolism has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Gene-targeted mice deficient in LCAT activities are associated with HTG in a gene dose-dependent manner (6,7). Transgenic mice (8) and rabbits (9) overexpressing human LCAT gene have been reported to have a modest reduction in fasting plasma triglycerides (TG). These observations suggest that LCAT may play an important role in modulating plasma TG levels, but the underlying mechanisms have not been explored.…”
Section: Hypertriglyceridemia (Htg)mentioning
confidence: 99%
“…Previous studies identified the brain as one of three organs that synthesize LCAT, together with liver and testes (6,9,(32)(33)(34)(35). In situ hybridization experiments showed that LCAT mRNA is present in neuronal and nonneuronal cell types in rhesus monkeys (9).…”
Section: Lcat Is Synthesized In Primary Murine Astrocytes and Neuronsmentioning
confidence: 99%
“…It is generally postulated that variation in plasma HDL-C levels are determined not by the rate at which they are produced, but rather by the rate of catabolism of their components. There are several known molecules that play a role in regulating plasma HDL-C levels (31), including HL (32)(33)(34)(35), LPL (36)(37)(38)(39)(40), lecithin:cholesterol acyl transferase (LCAT) (41,42), cholesterol ester transfer protein (CETP) (43), and phospholipid transfer protein (PLTP) (44). Intense study over the last few years has focused on the HDL particle in the context of reverse cholesterol transport and anti-oxidant properties, providing significant insights into the mechanism of HDL's antiatherogenic properties.…”
Section: Role In Lipoprotein Metabolismmentioning
confidence: 99%